2015
DOI: 10.3109/09687637.2015.1090397
|View full text |Cite
|
Sign up to set email alerts
|

Findings from mixed-methods feasibility and effectiveness evaluations of the “Breaking Free Online” treatment and recovery programme for substance misuse in prisons

Abstract: Reshaping substance misuse treatment in prisons is central to the UK Government's drive to address substance dependence in the prison population and reduce substance-related offending and recidivism. Therefore, a through-care project to support prisoners released from custody to community, ''Gateways'', is taking place across North-West England. Amongst support with housing, education, training and employment, Gateways incorporates the Breaking Free Online (BFO) substance misuse treatment programme. Aims: To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 60 publications
2
52
0
Order By: Relevance
“…Therefore many prisoners can be at risk from falling between the gaps in service provision. Therefore, the implementation of the BFHJ interventions, which have already shown some success for individuals experiencing difficulties with both mental health and substance misuse in terms of supporting them to strengthen their resilience and build recovery capital (Elison et al, 2015c), may provide an opportunity to engage and treat this particular population and their multiple and complex needs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore many prisoners can be at risk from falling between the gaps in service provision. Therefore, the implementation of the BFHJ interventions, which have already shown some success for individuals experiencing difficulties with both mental health and substance misuse in terms of supporting them to strengthen their resilience and build recovery capital (Elison et al, 2015c), may provide an opportunity to engage and treat this particular population and their multiple and complex needs.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of the more formal evaluation of the BFHJ programme (reported in Elison et al, 2015c), interviews also contained questions about participants views of this new treatment programme and how they feel it may have benefited them, and also ways in which they thought it could be refined and improved.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore if prisoners are transferred between prisons, or released to the community, they can continue to access the same interventions. Initial quantitative outcomes have indicated that engagement with BFO in the prison setting is associated with significant improvements to offenders quality of life, severity of substance dependence and other aspects of substance misuse recovery (Elison et al, 2015c).…”
Section: The Implications Of Recovery and Rehabilitation Capital For mentioning
confidence: 99%